Balboa Park, San Diego - James Blank::::::::: (Road Runner Card Co.)
Balboa Park, San Diego, California, is a great expanse of tree-covered hills and canyons full of beautiful floral displays and fanciful architecture. Here the Alcazar Gardens are shown before the California Tower, where the San Diego Museum of Man exhibits many of its treasures.